2019
DOI: 10.5546/aap.2019.eng.26
|View full text |Cite
|
Sign up to set email alerts
|

Effects of infant feeding practices and maternal characteristics on early childhood obesity

Abstract: Introduction. Early childhood obesity is a serious health problem not only because it causes serious health problems in children, but also because it poses a risk of obesity in the later stages of life. Objective. The aim of our study was to determine the effect of feeding (breastfeeding times, exclusive breastfeeding times, instances of night-time bottle feeding) and maternal characteristics (weight gain during pregnancy, BMI, socioeconomic status) on childhood overweight and obesity in children up to 36 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
(26 reference statements)
2
9
0
Order By: Relevance
“…A cohort study by Ardic et al found that early feeding habits might be permanent and pose a risk to later health outcomes. 26 In line with this study, Baran (2019), Pearce (2016) and Wang (2013) also found that breastfeeding less than 6 months and introducing adults' meals before 12 months were contributory factors for the prevalence of overweight and obesity in preschool children.…”
Section: Strengths and Limitations Of This Studysupporting
confidence: 65%
See 1 more Smart Citation
“…A cohort study by Ardic et al found that early feeding habits might be permanent and pose a risk to later health outcomes. 26 In line with this study, Baran (2019), Pearce (2016) and Wang (2013) also found that breastfeeding less than 6 months and introducing adults' meals before 12 months were contributory factors for the prevalence of overweight and obesity in preschool children.…”
Section: Strengths and Limitations Of This Studysupporting
confidence: 65%
“…The relationship between rapid weight gain and later childhood obesity further emphasises the potential programming that occurs very early in life, resulting in COO and associated health problems related to CF practices. A cohort study by Ardic et al found that early feeding habits might be permanent and pose a risk to later health outcomes 26. In line with this study, Baran (2019), Pearce (2016) and Wang (2013) also found that breastfeeding less than 6 months and introducing adults’ meals before 12 months were contributory factors for the prevalence of overweight and obesity in preschool children.…”
Section: Introductionsupporting
confidence: 64%
“…26,27 Characteristics of the included studies are presented in Table 1. The included studies were conducted primarily in the United States (US) (n = 5), [28][29][30][31][32][33] Australia (n = 2), 34,35 and Spain (n = 2), 36,37 while the remaining studies were carried out in Chile, 38 Kuwait, 39 Netherlands, 40 Turkey, 41 and the United Kingdom (UK). 42 The common primary outcome of the included studies were child and adolescent (ranging from 2 to 15 years of age) overweight/obese weight status (defined by WHO 43 or CDC 20 standards) and BMI status (measured as z-score, SDS, and/or percentiles).…”
Section: Resultsmentioning
confidence: 99%
“…29 Three studies reported family eating practices influenced child eating patterns and food preferences. 33,41,42 In a US study of 4815 children, Black children were significantly less likely to have daily family dinners together and more likely to have a higher BMI when compared to White children. 33 In a UK study, indulgent caregiver feeding style was related to a significantly higher child BMI z-score.…”
Section: Healthy Behaviours Lifestyle and Social Economic Statusmentioning
confidence: 99%
See 1 more Smart Citation